Influence of the multi-resolution technique on tomographic reconstruction in ultrasound tomography. Issue 6 (2nd November 2021) - Theu, Luong Thi; Tran, Quang-Huy; Solanki, Vijender Kumar; Shemeleva, Tatiana R.; Tran, Duc-Tan
Abstract : The greatest advantage of scattering theory-based ultrasound tomography (UT) is its ability to investigate small structures. DBIM is the Distorted Born Iterative Method. The nearest neighbour interpolation method is used to enhance the reconstruction performance and reduce the reconstruction time. The raw ( N 1  ×  N 1 ) and dense ( N 2  ×  N 2 ) meshed integration areas are reconstructed in NN 1 and NN 2 iterations, respectively. However, choosing the best value of NN 1 to get the highest performance was not mentioned in previous works. If it is not well chosen, the reconstruction quality is even worse than that when using no interpolation. This study proposes a method to enhance the UT reconstruction by using the nearest neighbour interpolation (MR-DBIM). The corresponding algorithms are specified by the graphical concurrent programming language of Sleptsov nets. Some significant results are (1) the MR-DBIM is only meaningful when r < 1 (i.e. sparse scattering domain); (2) the best performance is obtained in the DBIM when Nt  =  Nr, but in the MR-DBIM when Nr  = 2 Nt ; (3) the well-investigated value of NN 1 is 2 when 0.5 < r < 1 and is 3 when 0.2 < r < 0.5 . GRAPHICAL ABSTRACT: UF0001